On the relative density of clouds. (11th August 2017) - Jaramillo, Alejandro; Mesa, Oscar J.
Abstract : A simple analysis of the relative density of clouds with respect to dry and/or moist air is presented using modern and standard definitions. The results are consistent with current knowledge in atmospheric science and offer justification to common inadvertent simplifications used in the scientific literature.